Six-week anaerobic training improves proteolytic profile of diabetic rats - de Oliveira-Batista, Rogério [UNESP]; Silva, Angelita; dos Passos, Kaique Marques Rodrigues; Nogueira, Rosa Maria Barilli; Seraphim, Patricia Monteiro [UNESP] (Archives of Endocrinology and Metabolism, 2015)
Objective: To evaluate the effect of six-week anaerobic training on the mRNA expression of genes related to proteolysis Ubb (Ubiquitin), E2-14kDa, Trim63 (MuRF1 protein) and Nfkb1 in the skeletal muscle of diabetic rats. Materials and methods: Four groups were established: DE (Diabetes Exercised), DS (Diabetes Sedentary), CE (Control Exercised) and CS (Control Sedentary). The training consisted of 3 sets of 12 jumps in the liquid mean with load equivalent to 50% of BW for 6 weeks. Euthanasia occurred under ip anesthesia, and blood, adipose tissue and skeletal muscles were collected. Gene expression was quantified by RT-PCR in the gastrocnemius muscle. ANOVA one-way was used for comparison among groups, with post-hoc (Tukey) when necessary, considering p < 0.05. Results: We observed reduction in the body weight and adipose tissue in the diabetic groups. The muscle mass was reduced in DS, which could be reversed by training (DE). Although DS and DE have presented similar body weight, the training protocol in DE promoted reduction in the adipose tissue, and increase of muscle mass. Anaerobic training was efficient to reduce glycaemia only in the diabetic animals until 6 hours after the end of training. The Trim63 gene expression was increased in DS; decreased Ubb gene level was observed in trained rats (CE and DE) compared to sedentary (CS and DS), and DE presented the lowest level ​of E2-14kDa gene expression. Conclusion: Six-week anaerobic training promoted muscle mass gain, improved glycemic control, and exerted inhibitory effect on the proteolysis of gastrocnemius muscle of diabetic rats.
Keywords: Anaerobic training; Diabetes mellitus; Proteolysis; Skeletal muscle; Ubiquitin-proteasome